Electrical and morphological study of thermally evaporated (Sb2S3)1-xSnx thin films - Hasan, Bushra A. (Iraqi Journal of Physics, 2019)
(Sb2S3)1-xSnx thin films with different concentrations (0, 0.05 and 0.15) and thicknesses (300,500 and 700nm) have been deposited by single source vacuum thermal evaporation onto glass substrates at ambient temperature to study the effect of tin content, thickness and on its structural morphology, and electrical properties. AFM study revealed that microstructure parameters such as crystallite size, and roughness found to depend upon deposition conditions. The DC conductivity of the vacuum evaporated (Sb2S3)1-x Snx thin films was measured in the temperature range (293-473)K and was found to increase on order of magnitude with increase of thickness, and tin content. The plot of conductivity with reciprocal temperature suggests, there are three activation energies Ea1, Ea2 and Ea3 for (Sb2S3)1-x Snx for all x content values and thicknesses which decreases with increasing tin content and thickness. Hall effect measurement showed that low thickness (Sb2S3)1-x Snx film exhibit n-type conductance whereas the film exhibit p-type towards the higher thickness. The electric carrier concentration and mobility show opposite dependence upon tin content and thickness.